2014
DOI: 10.1016/j.compositesa.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Stress transfer efficiency in aligned multi-wall carbon nanotubes sheet/epoxy composites

Abstract: Stress transfer efficiency for 60 walls multi-walled carbon nanotube (MWNT) was calculated by the shear-lag theory. The results indicated that stress transfer between walls is insufficient at several tens of nanometer from the end; however stress converged to the same value for adequate length. Effective young's modulus was also calculated and indicated that MWNT can be treated as short fiber for over 20 m length (Aspect ratio > 400). The results implied that interfacial slippage or debonding area exists at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In the case of using sized fiber (B-S-NE and B-S-CNT specimens), more matrix debris were found to stick on the fiber surface as shown in Fig. 11b and c. This observation could be attributed to the high concentration of CNTs inside the sizing agent which improves the carbon fiber sheet/epoxy adhesion [55,56]. On the other hand, in the case of using sized fibers, little amount of epoxy resin were observed inside the fibers since coating the CF with a thin layer of sizing agent might influence their impregnation with the resin matrix.…”
Section: Flexural Behavior and Load-deflection Responsementioning
confidence: 63%
“…In the case of using sized fiber (B-S-NE and B-S-CNT specimens), more matrix debris were found to stick on the fiber surface as shown in Fig. 11b and c. This observation could be attributed to the high concentration of CNTs inside the sizing agent which improves the carbon fiber sheet/epoxy adhesion [55,56]. On the other hand, in the case of using sized fibers, little amount of epoxy resin were observed inside the fibers since coating the CF with a thin layer of sizing agent might influence their impregnation with the resin matrix.…”
Section: Flexural Behavior and Load-deflection Responsementioning
confidence: 63%
“…of the FRP composites by increasing the efficiency of load transfer between the fiber and the matrix. Fiber matrix interface plays a vital role in governing the overall properties of the composite and controls the behavior of the system under loading conditions [8]. Graphene (mono-layered, multi-layered) is also attracting the researchers due to its various properties [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Yang et al, specific monomer structure have major influence on the interaction between the CNT and the polymer, for the noncovalent binding of CNT into composite structures, polymers with a backbone containing aromatic rings can be used. As per Tsuda et al, MWNT can be treated as short fiber for over 20 μm length (aspect ratio > 400) and at the end of the MWNTs the interfacial slippage or debonding area exists. Prolongo et al reported that by charging the CNTs with positive nature (NH 3 + ), better mechanical properties can be obtained as compared to unmodified CNTS.…”
Section: Introductionmentioning
confidence: 99%